No impact of developmental conditions on serum estradiol levels among Bangladeshi women in the UK and Bangladesh. Issue 3 (26th June 2021) - Chaney, Carlye; Begum, Khurshida; Núñez‐de la Mora, Alejandra; Sievert, Lynnette L.; Muttukrishna, Shanthi; Harries, Victoria; Sharmeen, Taniya; Murphy, Lorna; Gunu, Richard; Chowdhury, Osul; Bentley, Gillian R.
Abstract: Introduction: While many aspects of female ovarian function respond to environmental stressors, estradiol (E2) appears less sensitive to stressors than progesterone, except under extreme ecological conditions. However, earlier studies relied on saliva samples, considered less sensitive than blood. Here, we investigated E2 variation among 177 Bangladeshi and UK white women, aged 35–59, using single serum samples. Bangladeshi women either grew up in Sylhet, Bangladesh (exposed to poor sanitation, limited health care, and higher pathogen loads but not poor energy availability), or in the UK. Methods: We collected samples on days 4–6 of the menstrual cycle in menstruating women and on any day for post‐menopausal women. Participants included: (i) Bangladeshi sedentees ( n = 36), (ii) Bangladeshis who migrated to the UK as adults ( n = 52), (iii) Bangladeshis who migrated as children ( n = 40), and (iv) UK white women matched for neighborhood residence to the migrants ( n = 49). Serum was obtained by venipuncture and analyzed using electrochemiluminescence. We collected anthropometrics and supplementary sociodemographic and reproductive data through questionnaires. We analyzed the data using multivariate regression. Results: E2 levels did not differ between migrant groups after controlling for age, BMI, physical activity, psychosocial stress, parity, and time since last birth (parous women). Paralleling results from salivary E2, serum E2 did not differ among women who experienced varying developmental conditions. Conclusion: Our results reinforce the hypothesis that E2 levels are stable under challenging environmental conditions. Interpopulation variation may only arise under chronic conditions of extreme nutritional scarcity, energy expenditure, and/or high disease burdens.